Increasing Students’ Vocabulary By Using Cartoon Technique At Seventh Grade Students Of SMP Dharmabudi Sidamanik - Benarita Purba; Juliani Saragih (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2022)
This research is describes about meaning Increasing Students’ Vocabulary By Using Cartoon Techanique At Seventh Grade Students of SMP Dharma Budi Sidamanik.The problem of the research isDoes using cartoon techanique can increase vocabulary for the seventh grade students of SMP Dharma Budi Sidamanik?. The objective of the research is to know whether using cartoon vocabulary technique can increase vocabulary for the seventh grade students of SMP Dharma Budi Sidamanik. The research was quantitative research. For the data collection, there were pre-test and post-test. The population of this research 100 students’ in academic year 2021 with of 25 students was the sample. The data analysis research was at seventh grade students stared from scoring pre-test and post-test and finding the diffrerent mean of the score. Based on the data analysis, the researcher finding the pre-test students mean score only 1188 and that mean was 47.52 and after the treatment, the researcher used to post-test to know students’ increase vocabulary in English score. The result of the test found the avarage of the post-test mean score test is 2010 that mean was 80,4. By Using cartoon technique in teaching vocabulary the students felt comfortable and enjoyed to learn new vocabulary and also can create students motivation and gives a good impact on other English skills